A Facile Surface Treatment to Improve the Abrasion Resistance of Photosensitive Film for Screen Printing. Issue 1 (2nd January 2019) - Li, Junlan; Zhao, Chunyan; Shen, Junhao; Wang, Hong; Pei, Gaimei; Xu, Shiai
Abstract: In this study, a facile surface treatment method was proposed to improve the abrasion resistance of photosensitive film for screen printing. Of the three silane coupling agents used in this study, 3-aminopropyltriethoxysilane (KH550) shows the best surface modification effect. The orthogonal experiments show that the concentration of KH550 solution is the most significant factor affecting the wear resistance of photosensitive films. Therefore, the surface characteristics and abrasion resistance of photosensitive films treated with various concentrations of KH550 solution were further investigated. The investigation shows that the abrasion resistance of photosensitive films treated with KH550 is improved greatly due to the existence of a coating on the surface, and it increases with the increase of KH550 concentration until a plateau is reached at a concentration of 15 wt%. The wear resistance of photosensitive films treated with 15 wt% of KH550 is increased by 34% compared with that of pure film. Moreover, surface treatment with KH550 leads to a decrease in surface roughness of photosensitive films and an increase in their hydrophobicity. Also, the hydrophobicity increases slightly with the increase of KH550 concentration, probably because KH550 concentration can only affect the thickness of surface coating, but has no effect on the surface property. This simple method is used for the first time to improve the abrasion resistance of photosensitive film, and it has the potential to be applied for large-scale production of durable screen plates.